The Role of Notaries in Making Limited Liability Company Legal Entity Deeds through the General Legal Administration System - Sumari, Sumari; Ma'ruf, Umar (Jurnal Konstatering, 2023)
Registration of limited liability company legal entity deeded from a manual system to an electronic system or online is expected so that the registration or validation can run more efficiently and more effectively. Similar to the previous provisions, until now the process of making a request for registration into the General Law Administration System still requires the role of a notary. The purpose of this paper is to analyze: 1) The role of the notary in drawing up limited liability company legal entity deeds through the general legal administration system in Blora Regency. 2) The effectiveness of making and registering limited liability company legal entity deeds by a notary through the general legal administration system in Blora Regency. The approach method in this research is a sociological juridical approach. The specification of the research used is descriptive analysis research. Types of data using primary data and secondary data. Data collection by interview method and literature study. The data analysis method used is qualitative analysis. The research problems were analyzed using the theory of legal certainty and the theory of legal effectiveness with the results of the research concluding: 1) The role of the notary in making legal entity deeds of limited liability companies through the General Legal Administration system in Blora Regency, namely making deeds and making applications electronically through the general law administration system, because a notary deed that functions as an authentic deed must provide certainty and legal protection for the community and function as the most perfect means of evidence.2) The effectiveness of making and registering limited liability company legal entity deeds by a notary through the General Legal Administration System in Blora Regency is the registration of limited liability company deeds through the General Legal Administration System by a notary directly which strongly supports a faster and more effective registration completion process. Keywords: Administration; Company; Entity; System.